Receptor activator of nuclear factor kappa B (RANK) as a determinant of peri-implantitis - Rakić Mia; Nikolić-Jakoba Nataša; Struillou Xavier; Petković-Ćurčin Aleksandra; Stamatović Novak; Matić Smiljka; Janković Saša; Aleksić Zoran; Vasilić Đurđa; Leković Vojislav; Vojvodić Danilo (Vojnosanitetski Pregled)
Background/Aim. Peri-implantitis presents inflammatory process that affects soft and hard supporting tissues of osseointegrated implant based on inflammatory osteoclastogenesis. The aim of this study was to investigate whether receptor activator of nuclear factor kappa B (RANK) concentrations in peri-implant crevicular fluid could be associated with clinical parameters that reflect inflammatory nature of peri-implantitis. Methods. The study included 67 patients, 22 with diagnosed peri-implantitis, 22 persons with healthy peri-implant tissues and 23 patients with periodontitis. Clinical parameters from each patient were recorded and samples of peri-implant/gingival crevicular fluid were collected for the enzyme-linked immunosorbent assay (ELISA) analysis. Results. RANK concentration was significantly increased in samples from the patients with periimplantitis when compared to healthy implants (p < 0.0001), where the average levels were 9 times higher. At the same time RANK concentration was significantly higher in periimplantitis than in periodontitis sites (p < 0.0001). In implant patients pocket depths and bleeding on probing values were positively associated with high RANK concentrations (p < 0.0001). Conclusion. These results revealed association of increased RANK concentration in samples of periimplant/ gingival crevicular fluid with peri-implant inflammation and suggests that RANK could be a pathologic determinant of peri-implantitis, thereby a potential parameter in assessment of peri-implant tissue inflammation and a potential target in designing treatment strategies.